Pregnancy-related outcomes for women with polycystic ovary syndrome - McDonnell, Rose (Womens Health (Lond), 2017)
The polycystic ovary syndrome is a common endocrine disorder that has profound implications for women throughout their reproductive years. A diagnosis of polycystic ovary syndrome is associated with reproductive challenges including a difficulty in conceiving as well as the pregnancy-related complications of miscarriage, hypertensive disorders, gestational diabetes and prematurity. Consequently, polycystic ovary syndrome has profound implications for women and their offspring with regard to reproductive function in the short term and in the longer term the risk of chronic illness and congenital anomalies, and health care resources should be directed accordingly to mitigate against these risks.